2013
DOI: 10.1002/ca.22255
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic description of the middle meatus and classification of the hiatus semilunaris into five types based upon morphological characteristics

Abstract: Anatomical variation of the lateral nasal wall, including the pathway from the frontal, ethmoidal, and maxillary sinuses may affect the communication between the paranasal sinuses and the nasal cavity. The middle meatus and hiatus semilunaris are areas where variations can occur which predispose patients to recurring sinusitis. Endoscopy allows for visualization of the entire nasal cavity, for both diagnostic and therapeutic uses. The purpose of this study was to provide an accurate characterization of the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Given that a sniff test is not only unreliable but also cannot be performed in patients who are unable to sniff, anterior meatuscopy is an attractive alternative. Using anterior meatuscopy, we revealed that the anterior INM is broader than the posterior INM, whereas the anterior MNM is narrower than the posterior MNM; these endoscopic observations are compatible with a cadaveric anatomical study 19 . We have also found that the anterior CNM is narrower than the posterior CNM, which is also consistent with an anatomical study demonstrating that the INT bone is thicker anteriorly than posteriorly 20 .…”
Section: Discussionsupporting
confidence: 85%
“…Given that a sniff test is not only unreliable but also cannot be performed in patients who are unable to sniff, anterior meatuscopy is an attractive alternative. Using anterior meatuscopy, we revealed that the anterior INM is broader than the posterior INM, whereas the anterior MNM is narrower than the posterior MNM; these endoscopic observations are compatible with a cadaveric anatomical study 19 . We have also found that the anterior CNM is narrower than the posterior CNM, which is also consistent with an anatomical study demonstrating that the INT bone is thicker anteriorly than posteriorly 20 .…”
Section: Discussionsupporting
confidence: 85%
“…Treatment of presurgical CRS patients with a local drug delivery system requires a small‐profile product that can fit into the tight anatomy of an unoperated patient without obstructing air flow. The average width of a middle meatus is reported to be 1.69 mm anteriorly, 2.83 mm at the transition angle, and 4.74 mm posteriorly . The LYR‐210 depot is a miniaturized local drug delivery system designed to fit within, and conform to, the confined space of a patient's middle meatus.…”
Section: Discussionmentioning
confidence: 75%
“…We have proposed a simple EMSS by anterior meatuscopy to select a meatus insertion tract for nasal anesthesia. In the anterior nasal cavity, the widths of the posterior meatuses, which are usually narrower than their anterior counterparts, are important . Other factors such as septum deviation or bony projection, mucosal or bony hypertrophy of the nasal turbinates, and the nasal cycle can also influence meatus patency.…”
Section: Discussionmentioning
confidence: 99%